Preparation method and application of anion-screened graphene oxide membrane
The oxygen-containing functional groups on the surface of graphene oxide nanosheets were removed by hydrothermal reduction and modified by polystyrene sulfonic acid. The anionic sieved graphene oxide film was stacked and prepared by vacuum filtration, which solved the anionic sieving performance of graphene oxide films in the anionic sieving process. Poor problems have achieved efficient anion sieving and water purification applications.
Patent Information
- Application Number
- CN202411232988.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-04
AI Technical Summary
The existing graphene oxide two-dimensional channel membranes have poor performance in anion sieving, which may be due to the hydrophilicity of the nanosheet surface, which leads to expansion and insufficient low-density negative charge, making it impossible to effectively screen anions.
Hydrothermal reduction method removes oxygen-containing functional groups on the surface of graphene oxide nanosheets, and increases negative charge through polystyrene sulfonic acid molecular chain modification, and stacks anionic sieved graphene oxide films to regulate two-dimensional channels. size and charge density.
The screening effect of anions is significantly improved, efficient ion selective transmission and water purification applications are achieved, and the screening performance of anions is improved through the synergistic effect of size screening and electrostatic repulsion.
Smart Images

Figure CN119186281A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new materials, and specifically relates to a preparation method and application of an anion screening graphene oxide membrane. Background Art
[0002] Ion screening technology has a wide range of applications in water purification systems, ion batteries, microfluidic systems, element extraction, reverse electrodialysis, energy conversion, biosensors, etc. Among them, anion screening also plays an irreplaceable role in various fields. A typical ion is the separation of chloride and sulfate in the chlor-alkali process. - / SO4 2- The separation is conducive to resource recovery and the acquisition of clean fresh water resources. Membrane separation technology has become an effective way to achieve ion screening due to its advantages of low energy consumption, high efficiency, and green environmental protection. Especially with the development of nanotechnology in recent years, membrane materials have made revolutionary progress, including two-dimensional nanomaterials, carbon nanotubes, nanofibers, metal organic frameworks, covalent organic frameworks, etc.
[0003] Among two-dimensional membrane materials, graphene oxide membranes show great potential in the field of ion screening due to their flexible and adjustable interlayer space and rich surface chemical properties. In addition, the abundant negatively charged oxygen-containing functional groups on the surface of graphene oxide nanosheets can screen anions through differences in electrostatic repulsion. However, it has been confirmed in practical applications that the anion screening performance of graphene oxide two-dimensional channel membranes is not as expected. There are two possible reasons: first, the hanging groups on the surface of graphene oxide nanosheets are hydrophilic and tend to attract water molecules, resulting in the expansion of two-dimensional nanochannels and the expansion of interlayer spacing; second, the low density of negative charges in graphene oxide nanochannels is not enough to produce sufficiently strong electrostatic repulsion with anions.
[0004] Therefore, it is necessary to develop a simple and effective method to precisely customize two-dimensional nanochannels with appropriate size and high negative charge density to achieve efficient screening of anions. Summary of the invention
[0005] In view of the above-mentioned problems existing in the prior art, the purpose of the present invention is to design and provide a technical solution for the preparation method and use of anion sieving graphene oxide membrane, which partially removes the oxygen-containing functional groups on the surface of graphene oxide nanosheets through a simple and green hydrothermal reduction method, and further uses polystyrene sulfonic acid molecular chains with negatively charged groups to modify the nanosheets, and uses a vacuum-assisted filtration method to stack and prepare anion sieving graphene oxide membrane with excellent separation performance.
[0006] The method for preparing an anion screening graphene oxide membrane is characterized by comprising the following steps: 1) Pour a graphene oxide nanosheet suspension with a concentration of 0.002-0.5 mg / ml into a reactor and heat it at a temperature of 90°C-180°C for 1-4 hours to obtain a reduced graphene oxide nanosheet suspension in which some oxygen-containing functional groups on the surface of the nanosheet are removed; The reduction temperature and time determine the reduction degree of the nanosheet. When the reduction degree is too high, the dispersibility of the nanosheet in the aqueous solution will decrease; in addition, when the reduction temperature is too high, the structure of the nanosheet will be destroyed; 2) uniformly mixing the suspension obtained in step 1) with a polystyrene sulfonic acid aqueous solution, wherein the concentration of the polystyrene sulfonic acid aqueous solution is 0.05-8.0 mg / ml, and the mass ratio of polystyrene sulfonic acid to graphene oxide nanosheets is 40-1:1, to obtain a suspension of reduced graphene oxide nanosheets modified with polystyrene sulfonic acid; when the concentration of polystyrene sulfonic acid is too low, it is not conducive to sufficient contact with the nanosheets, and when it is too high, too many molecular chains will be attached to the surface of the nanosheets, affecting the dispersion of the nanosheets; 3) The suspension obtained in step 2) is uniformly deposited on a porous substrate by vacuum-assisted filtration to form a membrane layer, and then dried to obtain an anion-sieving graphene oxide membrane.
[0007] The method for preparing an anion sieving graphene oxide membrane is characterized in that in step 1), the graphene oxide suspension is prepared by a modified Hummers method, and its concentration is 0.02-0.2 mg / ml, preferably 0.1-0.15 mg / ml.
[0008] The method for preparing an anion screening graphene oxide membrane is characterized in that in step 1): the graphene oxide nanosheet is a single-layer structure with a thickness of ~1nm and an average lateral size of ~5μm.
[0009] The method for preparing an anion screening graphene oxide membrane is characterized in that in step 1): the heating temperature is 100°C-150°C, preferably 110°C-120°C; and the heating time is 2-3h.
[0010] The method for preparing an anion sieving graphene oxide membrane is characterized in that in step 2), the concentration of the polystyrene sulfonic acid aqueous solution is 0.1-5 mg / ml, preferably 2-3 mg / ml.
[0011] The method for preparing an anion screening graphene oxide membrane is characterized in that in step 2), the mass ratio of polystyrene sulfonic acid: graphene oxide is 40-1:1, preferably 20-5:1.
[0012] The method for preparing an anion sieving graphene oxide membrane is characterized in that in step 3): the average pore size of the porous substrate is 50-500nm, preferably 100-200nm.
[0013] The method for preparing an anion screening graphene oxide membrane is characterized in that in step 3): in the vacuum assisted filtration method, the pressure is 0.05-0.6MPa, preferably 0.1-0.2MPa.
[0014] The method for preparing an anion sieving graphene oxide membrane is characterized in that in step 3), the drying temperature is 40-70°C and the drying time is 6-36h; preferably, the drying temperature is 60-65°C and the drying time is 12-20h. The appropriate drying temperature can remove the moisture in the membrane and make the nanosheets stack more tightly. However, when the temperature is too high, the nanosheets will be further reduced, affecting the interlayer spacing.
[0015] The anion screening graphene oxide membrane prepared by the method is applied in the fields of ion selective transmission and water purification.
[0016] The above-mentioned method for preparing anion-screening graphene oxide membrane removes some oxygen-containing functional groups on the surface of graphene oxide nanosheets by a physical hydrothermal reduction method, and further modifies the nanosheets with polystyrene sulfonic acid with rich charges, which can reasonably adjust the size of the two-dimensional channel when the nanosheets are stacked into a film, and at the same time enhance the negative charge inside the channel. The graphene oxide membrane prepared by the present invention not only has a stable and reasonably sized two-dimensional interlayer channel, but also has a high density of negative charges. Among them, the reasonable two-dimensional channel size is conducive to the transmission of monovalent anions, and the high-density negative charge can effectively prevent the passage of multivalent anions through size screening and electrostatic repulsion effects. The obtained two-dimensional channel stacking membrane has excellent ion screening performance and has good application prospects in the fields of ion selective transmission and water purification. When used for ion screening in the prior art, attention is often paid to the influence of a single factor such as the interlayer spacing of the two-dimensional graphene oxide channel or the charge distribution in the channel on the ion screening performance. The present invention proposes to make full use of the synergistic effect between the two, that is, the combined effect of the size screening effect and the charge repulsion effect, to achieve a high-efficiency ion screening effect. In addition, the technical solution of the present invention is simple and environmentally friendly. Only a controllable physical hydrothermal reduction method and a simple blending method (π-π stacking effect of two-dimensional nanosheets and polystyrene sulfonic acid molecular chains) are used to simultaneously achieve micro-regulation of the interlayer spacing of the graphene oxide membrane and the charge inside the channel, thereby significantly improving the screening effect of anions. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is an AFM comparison diagram of the original graphene oxide nanosheet, the reduced graphene oxide nanosheet, and the reduced graphene oxide nanosheet modified with polystyrene sulfonic acid molecular chains according to Example 1 of the present invention; Figure 2Schematic diagram of the mechanism and microstructure of different membranes in the ion screening process; Figure 3 This is a diagram showing the screening performance of anions at different mass ratios of graphene oxide nanosheets and polystyrene sulfonic acid. DETAILED DESCRIPTION
[0018] The present invention is described clearly and completely below in conjunction with the accompanying drawings and specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] The graphene oxide nanosheets in the present invention are prepared using the Hummers modified method. The graphene oxide sheet in the suspension has a single atomic layer thickness, a longitudinal dimension of ~1 nm, and a lateral dimension of ~5 μm. The modified Hummers method is a conventional means for preparing graphene oxide nanosheets.
[0020] Example 1 1) Dilute the graphene oxide nanosheet suspension prepared by the modified Hummers method to 0.2 mg / ml, take 25 ml of the diluted suspension and pour it into a 50 ml reactor, and heat it in an oven at 120°C for 3 hours. After cooling, the reduced graphene oxide nanosheet suspension is obtained. The AFM characterization results of the nanosheets are shown in Figure 1 As shown. The characterization results show that compared with the original graphene oxide nanosheets, the thickness of the reduced graphene oxide nanosheets is slightly reduced to about 0.9 nm, indicating that some oxygen-containing functional groups on the surface of the nanosheets have been removed; 2) The suspension obtained in step 1) above (25 ml, 0.2 mg / ml) was mixed with a 4 mg / ml polystyrene sulfonic acid aqueous solution at a volume ratio of 1:1, i.e., the mass ratio of polystyrene sulfonic acid to graphene oxide nanosheets was 1:20, and stirred at room temperature for 2 hours to obtain a suspension of reduced graphene oxide nanosheets modified with polystyrene sulfonic acid. The polystyrene molecular chain has benzene rings, which can be combined with the benzene rings on the reduced graphene oxide nanosheets by π-π interaction. The AFM image of the further modified nanosheets is shown in Figure 1 . From the characterization results, we can see that the thickness of the nanosheets has increased to about 1.2nm, indicating that the polystyrene sulfonic acid molecular chains are adsorbed on the surface of the nanosheets; 3) Take 4 ml of the suspension obtained in step 2) and dilute it to 50 ml with deionized water, use vacuum-assisted filtration to deposit the nanosheets on the porous cellulose substrate, and then transfer the separation layer with the substrate to an oven at 60°C and dry it for 12 hours to obtain an anion sieving membrane.
[0021] The prepared membrane was tested in anion screening experiments. Under the conditions of 0.1 mol / l concentration on the feed side, Cl - The permeation rate is 0.91 mol m -2 h -1 , Cl - / SO4 2- The selectivity is 80.8.
[0022] Example 2 The specific steps are the same as those in Example 1, except that in step 2), 25 ml of the 0.2 mg / ml suspension and a 0.2 mg / ml polystyrene sulfonic acid aqueous solution are mixed in equal volumes, that is, the mass ratio of polystyrene sulfonic acid:graphene oxide nanosheets is 1:1.
[0023] Furthermore, the prepared membrane was tested in anion screening experiment. Under the condition that the concentration of Cl on the feed side was 0.1 mol / l, - The permeation rate is 1.14 mol m -2 h -1 , Cl - / SO4 2- The selectivity is 2.9, such as Figure 3 It can be seen that when the mass ratio of polystyrene sulfonic acid to reduced graphene oxide nanosheets is low, Cl - / SO4 2- The selectivity of Cl is also low. This shows that when the negative charge in the channel is low, it is not conducive to - / SO4 2- Selective screening.
[0024] Example 3 The specific steps are the same as those in Example 1, except that in step 2), 25 ml of the 0.2 mg / ml suspension and a 1.0 mg / ml polystyrene sulfonic acid aqueous solution are mixed in equal volumes, that is, the mass ratio of polystyrene sulfonic acid:graphene oxide nanosheets is 5:1.
[0025] Furthermore, the prepared membrane was tested in anion screening experiment. Under the condition that the concentration of Cl on the feed side was 0.1 mol / l, - The permeation rate is 1.06 mol m -2 h -1 , Cl - / SO4 2- The selectivity is 6.7, such as Figure 3 This indicates that the negative charge of the membrane prepared at this ratio is still insufficient, resulting in Cl - / SO4 2- The options are still limited.
[0026] Example 4 The specific steps are the same as those in Example 1, except that in step 2), 25 ml of the 0.2 mg / ml suspension and an 8.0 mg / ml polystyrene sulfonic acid aqueous solution are mixed in equal volumes, that is, the mass ratio of polystyrene sulfonic acid: graphene oxide nanosheets is 20:1.
[0027] Furthermore, the prepared membrane was tested in anion screening experiment. Under the condition that the concentration of Cl on the feed side was 0.1 mol / l, - The permeation rate is 0.21 mol m -2 h -1 , Cl - / SO4 2- The selectivity is 66.0, such as Figure 3 It should be noted that in this embodiment, when the mass ratio of polystyrene sulfonic acid to graphene oxide nanosheets increases to 40:1, Cl - The permeation rate of Cl - / SO4 2- The selectivity of Cl - / SO4 2- Selective screening.
[0028] Example 5 Step 1) dilute the graphene oxide nanosheet suspension prepared by the modified Hummers method to 0.2 mg / ml, take 25 ml of the diluted suspension and pour it into a reactor with a capacity of 50 ml, and place it in an oven at 90° C. and heat it for 4 hours. After cooling, a reduced graphene oxide nanosheet suspension is obtained.
[0029] The remaining steps are the same as those in Example 1.
[0030] Furthermore, the prepared membrane was tested in anion screening experiment. Under the condition that the concentration of Cl on the feed side was 0.1 mol / l, - The permeation rate is 0.76 molm -2 h -1 , Cl - / SO4 2- The selectivity is 8.5. Note that in this embodiment, due to the low reduction degree of the nanosheets, the interlayer spacing is not effectively controlled, making Cl - / SO4 2- The selectivity is low.
[0031] Example 6 Step 1) dilute the graphene oxide nanosheet suspension prepared by the modified Hummers method to 0.2 mg / ml, take 25 ml of the diluted suspension and pour it into a reactor with a capacity of 50 ml, and place it in an oven at 180° C. and heat it for 1 hour. After cooling, a reduced graphene oxide nanosheet suspension is obtained.
[0032] The remaining steps are the same as those in Example 1.
[0033] Furthermore, the prepared membrane was tested in anion screening experiment. Under the condition that the concentration of Cl on the feed side was 0.1 mol / l, - The permeation rate is 0.04 mol m -2 h -1 , Cl - / SO4 2- The selectivity is 12.6. In this embodiment, due to the high reduction degree of the nanosheets, the interlayer spacing is sharply reduced, and Cl - and SO4 2- The transmission of Cl - / SO4 2- The selectivity is low.
[0034] It can be seen from Examples 5 and 6 that the control of the reduction degree of the nanosheets is also an important part of the present invention.
[0035] Comparative Example 1 The original graphene oxide nanosheet suspension of the same volume and concentration as in Example 1 (i.e., 4 ml of 0.1 mg / ml) was diluted to 50 ml with deionized water, and the nanosheets were further deposited onto the porous cellulose ester substrate using a vacuum filtration method. The separated layer with the substrate was transferred to an oven at 60° C. and dried for 12 h to obtain a original graphene oxide membrane.
[0036] Furthermore, the prepared membrane was tested in anion screening experiments. Under the conditions of 0.1 mol / l concentration on the feed side, Cl - The permeation rate is 1.09 molm -2 h -1 , Cl - / SO4 2- The selectivity is 1.4. It can be seen that although the original graphene oxide film Cl - The permeation rate is higher, but the - / SO4 2- There is almost no selectivity. This is because the interlayer spacing of the original graphene oxide film is not precisely controlled and its negative charge is weak.
[0037] Comparative Example 2 Step 1) dilute the graphene oxide nanosheet suspension prepared by the modified Hummers method to 1.0 mg / ml, take 25 ml of the diluted suspension and pour it into a reactor with a capacity of 50 ml, and place it in an oven at 120° C. and heat it for 3 hours. After cooling, a reduced graphene oxide nanosheet suspension is obtained.
[0038] It can be observed that the reduced graphene oxide nanosheet suspension prepared by the physical hydrothermal method at this concentration exhibits serious agglomeration and cannot form a film. Therefore, it can be seen that the concentration control and selection of graphene oxide before reduction is also an important part of the present invention.
[0039] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing anion screening graphene oxide membrane, characterized in that The following steps are involved: 1) pouring a graphene oxide nanosheet suspension having a concentration of 0.002-0.5 mg / ml into a reaction vessel and heating the suspension at a temperature of 90° C. to 180° C. for 1-4 hours to obtain a reduced graphene oxide nanosheet suspension having some oxygen-containing functional groups on the surface of the nanosheet removed; 2) uniformly mixing the suspension obtained in step 1) with a polystyrene sulfonic acid aqueous solution, wherein the concentration of the polystyrene sulfonic acid aqueous solution is 0.05-8.0 mg / ml, and the mass ratio of polystyrene sulfonic acid to graphene oxide nanosheets is 40-1:1, to obtain a polystyrene sulfonic acid-modified reduced graphene oxide nanosheet suspension; 3) The suspension obtained in step 2) is uniformly deposited on a porous substrate by vacuum-assisted filtration to form a membrane layer, and then dried to obtain an anion-sieving graphene oxide membrane.
2. A method for preparing an anion screening graphene oxide membrane as described in claim 1, characterized in that In step 1), the graphene oxide nanosheet suspension is prepared by a modified Hummers method, and its concentration is 0.02-0.2 mg / ml, preferably 0.1-0.15 mg / ml.
3. A method for preparing an anion screening graphene oxide membrane as described in claim 1, characterized in that In step 1), the graphene oxide nanosheet is a single-layer structure with a thickness of ~1 nm and an average lateral size of ~5 μm.
4. A method for preparing an anion screening graphene oxide membrane as described in claim 1, characterized in that In step 1), the heating temperature is 100°C-150°C, preferably 110°C-120°C; the heating time is 2-3h.
5. A method for preparing an anion screening graphene oxide membrane as described in claim 1, characterized in that In step 2), the concentration of the polystyrene sulfonic acid aqueous solution is 0.1-5 mg / ml, preferably 2-3 mg / ml.
6. A method for preparing an anion screening graphene oxide membrane as described in claim 1, characterized in that In step 2), the mass ratio of polystyrene sulfonic acid:graphene oxide is 40-1:1, preferably 20-5:
1.
7. A method for preparing an anion screening graphene oxide membrane as described in claim 1, characterized in that In step 3), the average pore size of the porous substrate is 50-500 nm, preferably 100-200 nm.
8. A method for preparing an anion screening graphene oxide membrane as described in claim 1, characterized in that In step 3): in the vacuum-assisted filtration method, the pressure is 0.05-0.6 MPa, preferably 0.1-0.2 MPa.
9. A method for preparing an anion screening graphene oxide membrane as described in claim 1, characterized in that In step 3), the drying temperature is 40-70°C and the drying time is 6-36h; preferably, the drying temperature is 60-65°C and the drying time is 12-20h.
10. Application of the anion screening graphene oxide membrane prepared by the method as described in claim 1 in the fields of ion selective transport and water purification.
Citation Information
Patent Citations
Modified graphene film applied to monovalent and polyvalent metal ion separation and preparation method thereof
CN107261857A
Preparation method of stable and anti-pollution monovalent selective anion exchange membrane
CN108176250A
Zwitter-ion modified graphene oxide double-layer structure composite membrane as well as preparation method and application thereof
CN115518523A
Preparation method and application of heteropolyacid molecular cluster intercalated reduced graphene oxide separation membrane
CN117379989A
